O CARÁTER TRANSVERSAL DO ENSINO DO EMPREENDEDORISMO NAS PRÁTICAS DE FORMAÇÃO PROFISSIONAL DE GRADUAÇÃO TECNOLÓGICA DO ESTADO DE SÃO PAULO - MEDEIROS, MARIA DA CONCEIÇÃO (2019)
The socio-economic, political and environmental scenario experienced in the last decades, directed the attention to the transformations that occurred in the behavior and positioning of society and organizations. Demands emerge from a professional profile that is able to respond with competencies to new forms of work relations, as well as to new models of production and commercialization of goods and services in a global market. The concepts of employability, entrepreneurship and innovation (SCHUMPETER, 1997; DELORS, 2012; DORNELAS, 2018) when associated with this panorama, they assume relevance in the interaction with the individual and with the environment, becoming essential the constant improvement directed to the different aspects that involve society. The entrepreneurial action is highlighted as an option for adaptation and inclusion in this new conjuncture, attracting the interest of organizations and society in relation to the theme. In this context, the understanding of new forms of work and income generation, has become an important fact for the understanding of the modern arrangements of society related to work, to the environment of organizations and their collaborators (VALE, 2014; SUSSKIND, 2017), a movement that requires constant actions, which respond to the impositions of competition in a global market. Thus, the study aimed to identify by means of a qualitative research of exploratory-descriptive nature the insertion of the theme entrepreneurship in the formation of higher technological graduation through transversality as teaching methodology. The instrument for data collection was due to the use of semi-structured interviews, opting for data analysis by discourse analysis, a methodology that has been used by organizational researchers. To meet the objectives established for the study, we defined as participants of the research professors’ coordinators of pedagogical projects related to discussion, analysis, reflection and formulation of pedagogical and curricular proposals of technological graduation of an institution of higher public education of technological graduation of the state of São Paulo. The analysis of the data obtained in the research revealed that the assumptions of entrepreneurial education, as pointed out by Dornelas (2018) and Dolabela (2006), constitute an alternative path to respond to the new demands arising from the productive sector and New work relations, pointing out that the insertion of the theme entrepreneurship in the formation of technological graduation, is perceived as a good time for the development of the entrepreneurial profile. Transversality is understood and accepted as a mechanism of integration, configuring itself in a viable methodology for the development of entrepreneurial education, however it was not possible to identify its applicability in the pedagogical practices of the units of Teaching of the institution